Quand la compétence traductologique dépasse la compétence rédactionnelle - Tomaszkiewicz, Teresa (Wydawnictwo Naukowe UAM, 2003)
This article discusses a characteristic style of John Paul II' homilies, delivered during his first pilgrimage to Poland in 1979. The author touches the question of the censorship who had an influence on the way of translating these texts and ponders the limits of liberty and faithfulness of a translator who prepares his translations in a definite social and political context.
How the translational competence surpasses editorial competence
Keywords: Translational competence; Editorial competence